Risky Business: Venture Capital, Pivoting and Scaling - Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (CESifo GmbH, 2024)
The creation and scaling of startups are inherently linked to risk-taking, with various types of owners handling these risks differently. This paper investigates the influence of an active venture capital (VC) market on startups' decisions regarding research and scaling. It outlines conditions under which VC-backed startups prefer riskier, yet potentially more rewarding strategies compared to independent startups. VC firms, by means of temporary ownership and compensation structures, introduce ”exit costs” that make high-risk strategies more attractive to VC-backed startups. Moreover, an active VC market prompts startups to undertake higher initial risks, as VC firms provide support for pivoting after setbacks. Additionally, the presence of VC intensifies research risk among established firms, as their research initiatives are strategic complements to the risk choices of startups.
Keywords: G24; L26; M13; 330; entrepreneurship; pivoting; research; scaling; venture capital